Serum Metabolomics Analysis of the Anti-Inflammatory Effects of Gallic Acid on Rats With Acute Inflammation - Wu, Yue; Li, Kuangyu; Zeng, Maolin; Qiao, Boyang; Zhou, Benhong (Frontiers in Pharmacology, 2022)
Background: Gallic acid (GA) is a natural small-molecule polyphenol having a wide range of pharmacological activities. Until now, some works have studied the effect and the mechanisms of GA against inflammation. However, whether or how gallic acid regulates the downstream metabolic disorder against acute inflammation remains unclear. The present study explored the protective effect and the potential mechanism of GA on acute inflammation through the metabolomics approach. Methods: An acute inflammation rat model was induced by local injection of carrageenin. Local swelling on paw and serum tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) were assessed in Control, Model and Gallic acid groups, respectively. Serum metabolomics based on high-performance liquid chromatography coupled with mass spectrometry (HPLC-MS) was also established to collect rats’ metabolic profiles and explore the metabolic changes related to GA pretreatment. Results: Compared to the Modal group, local pain, redness, and swelling induced by carrageenin were significantly alleviated in GA groups in addition to the dose-dependent decreases of TNF-α and IL-6. Metabolomics analysis found significant alterations in metabolic signatures between the carrageenin-induced inflammation and control groups. Twelve potential biomarkers were further identified in acute inflammation by principal component analysis (PCA) and partial least squares discrimination analysis (PLS-DA). In addition, when rats were pretreated with gallic acid, serum levels of eleven biomarkers were observed to restore partially. Metabolic pathway and networks analysis revealed that GA might invert the pathological process of acute inflammation by regulating the key biomarkers involved in linoleic acid metabolism, ascorbate and aldarate metabolism, pentose and glucuronate interconversions, and arachidonic acid (AA) metabolism pathways. Conclusion: The study elucidates the protective effect of gallic acid against acute inflammation and its possible regulating mechanism from a metabolomic perspective. These results could provide a theoretical basis for clarifying gallic acid’s mechanism and potential medicinal value in curing inflammation disorder in the clinic.